(untitled) (Ameghiniana, 2014)
The Punta Negra Formation, considered Early-Middle Devonian in age, represents the latest Devonian unit, unconformably underlying the Carboniferous Tupe Formation, at the central sector of the Argentine Precordillera. The thick siliciclastic deltaic unit, with rare shelly fossils, has yielded the brachiopods Dagmachonetinae indet., Discinidae indet., Metaplasia? sp., Mutationella sp., and Salopina sp. In spite of the provisional identification of most of this scarce material, it allows us to substantiate an Early Devonian age (probably latest Emsian) for the lower part of the Punta Negra Formation.